2002
DOI: 10.1097/00004836-200201000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Esophageal Varices in Patients With Cirrhosis

Abstract: The prevalence of EV in cirrhosis increases with the severity of liver disease, as expected. Thrombocytopenia and splenomegaly are independent predictors of large EV in cirrhosis. Further prospective studies might result in a discriminating algorithm to predict which patients with cirrhosis would benefit from early or regular endoscopy to detect clinically significant varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
147
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(172 citation statements)
references
References 28 publications
17
147
1
7
Order By: Relevance
“…It may be explained according to the issue that palpable spleen as well as LEV may both be related to the presence of a higher portal pressure. Different factors found to be important for this purpose included splenomegaly [23][24][25][26][27][28] , thrombocytopenia [23][24][25][26][27][28][29][30] , ascites [25,27] , hepatic encephalopathy [25] , serum albumin concentration [30] , serum bilirubin levels [30] , and Child-Pugh score [27,28] . Thus, the results of our study are consistent with those of the previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…It may be explained according to the issue that palpable spleen as well as LEV may both be related to the presence of a higher portal pressure. Different factors found to be important for this purpose included splenomegaly [23][24][25][26][27][28] , thrombocytopenia [23][24][25][26][27][28][29][30] , ascites [25,27] , hepatic encephalopathy [25] , serum albumin concentration [30] , serum bilirubin levels [30] , and Child-Pugh score [27,28] . Thus, the results of our study are consistent with those of the previously published data.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18] Three of the four studies with higher sensitivities had poor specificity. In a study by Madhotra et al, 17 Fig. 4.…”
Section: Discussionmentioning
confidence: 98%
“…Platelet counts (PLT) from 68,000 to 160,000 have shown sensitivities ranging from 71% to 88% for small varices. [14][15][16][17][18] The sensitivities for large varices are better but with unsatisfactory specificities. However, many of these studies were crosssectional and were limited by the variability and severity of the liver disease.…”
mentioning
confidence: 99%
“…Several studies (13)(14)(15)(16)(17)(18)(19) have shown that platelet count and spleen diameter correlate well with the presence of EVs. However, in patients with chronic liver disease, the presence of a decreased platelet count may depend on several factors other than portal hypertension, such as shortened mean platelet lifetime, decreased thrombopoietin production or myelotoxic effects of alcohol or hepatitis viruses (20).…”
Section: Discussionmentioning
confidence: 99%